2000
DOI: 10.1007/s005950070060
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Small Aneurysms of the Internal Iliac Artery Following Proximal Ligation in Abdominal Aortic Aneurysm Repair

Abstract: To assess the natural history of small internal iliac artery aneurysms (IIAA) measuring 2.0-3.0 cm in diameter, proximally ligated in association with abdominal aortic aneurysm (AAA) repair, we examined 9 of 12 patients who underwent this type of surgery. Postoperative computed tomography scanning demonstrated that three IIAAs were still patent and the other six were thrombosed. An increase in the maximum diameter from that at the time of surgery was seen in four IIAAs. One patient suffered serious complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Natural history of IIAAs following proximal ligation has been infrequently reported with significant enlargement in nearly 50% of patients. 18 Two of 25 patients in our series presenting with isolated IIAAs (4.3 and 4.2 cm diameter) had undergone AAA repair by us 4 and 10 years previously when the small IIAAs were left untreated. Both patients underwent successful endovascular repair (Fig 7, C).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Natural history of IIAAs following proximal ligation has been infrequently reported with significant enlargement in nearly 50% of patients. 18 Two of 25 patients in our series presenting with isolated IIAAs (4.3 and 4.2 cm diameter) had undergone AAA repair by us 4 and 10 years previously when the small IIAAs were left untreated. Both patients underwent successful endovascular repair (Fig 7, C).…”
Section: Discussionmentioning
confidence: 88%
“…These aneurysms were often simply treated with proximal ligation and aortoiliac/femoral bypass when associated with AAAs and CIAAs, allowing subsequent growth of the IIAA sac from retrograde, cross-pelvic collateral flow. [17][18][19] The introduction of minimally invasive endovascular options have opened up other simpler, less morbid avenues of treatment with coil embolization of the outflow and therapeutic exclusion of the IIAA sac, but sacrifice of internal iliac artery (IIA) flow has also brought to light issues of acute and chronic pelvic ischemic syndromes.…”
mentioning
confidence: 99%
“…1,2) In the present case, a 6 cm aneurysm redeveloped in an IIA aneurysm that had been excluded from the circulation by proximal ligation 16 years prior to the current presentation. Surgical access is considered difficult in patient with previous laparotomies and those with large bilateral IIA aneurysms, and coil embolization is an appropriate intervention in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Darling et al reported that 4% of excluded AAAs had persistent blood flow in the aneurysm sac and 0.6% of these aneurysm went on to rupture. 6) In the present case, the persistent flow may be related to the superior gluteal artery, the inferior gluteal artery and the obturator artery serving as inflow and outflow conduit, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation